Implementasi Sistem Kontrol PID untuk Orientasi Robot Hexapod - Adriansyah, Yoga; Senanjung Prayoga; Anugerah Wibisana (Journal of Applied Electrical Engineering, 2025)
This research aims to improve the stability and accuracy of hexapod robot motion in the SAR competition in Indonesia using an adaptive PID control system combined with fuzzy logic. PID control has advantages in linear systems but is less responsive to dynamic conditions, while fuzzy logic can produce a more flexible adaptive response. The proposed system uses IMU sensors to measure directional error, where this data is then processed by fuzzy control to adjust the PID parameters in real time. Tests show that this method results in an average recovery time of 3,06 seconds, a rise time of 1,99 seconds, and an overshoot of approximately 10,00% to 15,60%. These results show an increase in the efficiency of the robot in navigating in complex environments, thus improving the performance in real applications.